(untitled) (Bangladesh Journal of Botany, 2021)
A pot experiment was conducted to compare the efficacy of some products i.e., Stanes Bio Nematon®, Soft Guard®, Paecilomyces lilacinus, Trichoderma longibranchiatum, camel and goat manures against Meloidogyne javanica on tomato under greenhouse conditions. Based on nematode reproduction, indices of galls and egg masses, the six materials were grouped into four classes from the relatively highest efficacy of control (goat manure) to the relatively low efficacy of control (P. lilacinus). Bangladesh J. Bot. 50(3): 709-712, 2021 (September)